Fiscal fault, financial fix? Capital Markets Union and the quest for macroeconomic stabilization in the euro area - Benjamin Braun; Marina Hübner (Max Planck Institute for the Study of Societies, 2017)
This paper argues that Capital Markets Union - the EU's attempt to establish a more marketbased financial system - is a result less of financial policymaking than of macroeconomic governance in a politically fractured polity. The current governance structure of Economic and Monetary Union (EMU) severely limits the capacity of both national and supranational actors to provide a core public good, macroeconomic stabilization. While member states have institutionalized fiscal austerity and abandoned other macroeconomic levers, the European polity lacks the fiscal resources necessary to achieve stable macroeconomic conditions: smoothing the business cycle, ensuring growth and job creation, and mitigating the impact of asymmetric output shocks on consumption. Capital Markets Union, we argue, is an attempt by European policymakers to devise a financial fix for this structural capacity gap. Using its regulatory powers, the European Commission, supported by the European Central Bank (ECB), seeks to harness private financial markets and instruments to provide the public policy good of macroeconomic stabilization. We trace how technocrats, think tanks, and financial-sector lobbyists, through the strategic use of knowledge and expertise, established securitization and market-based finance as solutions to EMU's governance problems. – – Woher rührt das politische Streben in Brüssel nach einer Kapitalmarktunion und damit nach einem stärker marktbasierten europäischen Finanzsystem? Dieser Aufsatz legt dar, dass es sich nicht in erster Linie um ein finanzmarktpolitisches Projekt handelt, sondern um ein Projekt makroökonomischer Steuerungspolitik innerhalb eines fragmentierten Mehrebenensystems. Die Struktur der Europäischen Wirtschafts- und Währungsunion (EWU) beschneidet Steuerungskapazitäten auf der nationalen Ebene, ohne sie auf der supranationalen Ebene zu stärken. National verordnete fiskalische Austerität in Kombination mit dem Verlust anderer Steuerungshebel haben in der Eurozone ein institutionelles Umfeld geschaffen, in dem die notwendigen fiskalischen Ressourcen zur Gewährleistung stabiler makroökonomischer Bedingungen fehlen - allen voran Konjunkturglättung und Wachstumsförderung. Das Projekt Kapitalmarktunion, so unser zentrales Argument, ist der Versuch europäischer Entscheidungsträger, diese strukturelle Kapazitätslücke mit den zur Verfügung stehenden regulativen Mitteln zu füllen. Konkret versucht die Europäische Kommission, unterstützt durch die Europäische Zentralbank, das öffentliche Gut makroökonomischer Stabilität über den Umweg privater Finanzmärkte und Finanzinstrumente zu erreichen. Im Rahmen einer detaillierten Prozessanalyse zeichnen wir nach, wie Technokraten, Think Tanks und Finanzlobbyisten Wissen und Expertise mobilisierten, um Kreditverbriefung und marktbasierte Finanzierung als Lösungen für die Steuerungsdefizite der EWU zu etablieren.
hdl:21.11116/0000-0000-B0EC-F
Keywords: 300; regulation; securitization; euro area; fiscal policy; financial markets; European Commission; ECB; Regulierung; Kreditverbriefung; Euroraum; Steuerpolitik; Finanzmärkte; Europäische Kommission; Europäische Zentralbank